Seaweed in the Diet as a Source of Bioactive Metabolites and a Potential Natural Immunity Booster: A Comprehensive Review - Amiya Kumar Mandal; Sudhamayee Parida; Akshaya Kumar Behera; Siba Prasad Adhikary; Andrey A. Lukatkin; Alexander S. Lukatkin; Mrutyunjay Jena (Pharmaceuticals)
Seaweed plays an essential role in the survival of marine life, provides habitats and helps in nutrient recycling. It is rich in valuable nutritious compounds such as pigments, proteins, polysaccharides, minerals, vitamins, omega-rich oils, secondary metabolites, fibers and sterols. Pigments like fucoxanthin and astaxanthin and polysaccharides like laminarin, fucoidan, galactan and ulvan possess immune-modulatory and immune-enhancing properties. Moreover, they show antioxidative, antidiabetic, anticancer, anti-inflammatory, antiproliferative, anti-obesity, antimicrobial, anticoagulation and anti-aging properties and can prevent diseases such as Alzheimer’s and Parkinson’s and cardiovascular diseases. Though seaweed is frequently consumed by Eastern Asian countries like China, Japan, and Korea and has gained the attention of Western countries in recent years due to its nutritional properties, its consumption on a global scale is very limited because of a lack of awareness. Thus, to incorporate seaweed into the global diet and to make it familiar as a functional food, issues such as large-scale cultivation, processing, consumer acceptance and the development of seaweed-based food products need to be addressed. This review is intended to give a brief overview of the present status of seaweed, its nutritional value and its bioactive metabolites as functional foods for human health and diseases owing to its immunity-boosting potential. Further, seaweed as a source of sustainable food and its prospects along with its issues are discussed in this review.